A Normative Approach to Bank Capital Adequacy - Talmor, Eli (Journal of Financial and Quantitative Analysis, 1980)
Eli Talmor, A Normative Approach to Bank Capital Adequacy, The Journal of Financial and Quantitative Analysis, Vol. 15, No. 4, Proceedings of 15th Annual Conference of the Western Finance Association, June 19-21, 1980, San Diego, California (Nov., 1980), pp. 785-811